Cold energy recovery in an LNG plant - Mahadzir, Shuhaimi (AIDIC, 2009)
This paper prroposes an initiative to maximize the production of LNG and other byproducts in an LNG complex. Using the concept of cold recovery, the cold stream from the scrub column bottoms in the gas liquefaction proces was used as a heat sink.